Is There Profit from Bonus Share Announcements in Nairobi Securities Exchange? - Ndegwa, James N.; Kiweu, Joséphat M. (Research Journal of Finance and Accounting, 2013)
The question of whether the announcement of issuance of bonus shares by quoted companies is news to stock market participants or it is anticipated by the market has been the subject of research. If the announcement is anticipated, then stock prices should not change drastically during the days surrounding the announcement date. This research employed the event study methodology by using the bonus announcements of eighteen NSE listed companies that occurred during the year 2005 to 2010. The t-test statistic was employed to test the significance of the average abnormal returns and cumulative average abnormal returns from zero. It is possible to profit from bonus share announcement when the abnormal or abnormal returns are significant from zero. The results of ttests on the average abnormal return (AAR) and the cumulative average abnormal return (CAAR) indicated that abnormal returns were significantly different from zero which implied that implied that there is an anomaly in the semi-strong form efficiency of the NSE with regards to bonus announcements as it is possible to profit from such announcements which is regarded as news by NSE investors.